2022
DOI: 10.3390/jcm11030504
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Acute Myeloid Leukemia—Past, Present, and Future

Abstract: This review reports about the main steps of development in pediatric acute myeloid leukemia (AML) concerning diagnostics, treatment, risk groups, and outcomes. Finally, a short overview of present and future approaches is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 111 publications
(121 reference statements)
0
33
0
7
Order By: Relevance
“…Over the last few decades, there has been a significant improvement in survival in pediatric AML in highincome countries (HICs) [2]. This improvement has been achieved through better risk stratification, improved supportive care, and allogeneic hematopoietic stem cell transplantation (HSCT) [3,4]. The outcomes of pediatric AML in low-income countries (LICs) and low and middle-income countries (LMICs) have been poor compared to HICs due to limited resources, high cost of treatment, infections, lack of access to allogeneic HSCT, delayed and moribund presentation, and treatment abandonment [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, there has been a significant improvement in survival in pediatric AML in highincome countries (HICs) [2]. This improvement has been achieved through better risk stratification, improved supportive care, and allogeneic hematopoietic stem cell transplantation (HSCT) [3,4]. The outcomes of pediatric AML in low-income countries (LICs) and low and middle-income countries (LMICs) have been poor compared to HICs due to limited resources, high cost of treatment, infections, lack of access to allogeneic HSCT, delayed and moribund presentation, and treatment abandonment [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment decisions are based on risk stratification and further guided by the initial response to treatment [ 5 , 6 , 23 ]. Most international pediatric study groups (AIEOP/BFM/FRANCE/UK/COG/Japan) define risk classification according to genetic/molecular abnormalities and response to treatment by the measurement of residual disease by flow and morphology [ 24 ]. In particular, favorable prognostic factors include t(8;21)(q22;q22)/RUNX1-RUNX1T1, t(15;17)(q22;q21)/PML-RARA, NPM1-mutated AML, and CEBPA double mutation [ 6 ].AML with MLL translocations has variable outcomes, depending on the associated translocation and occurs more frequently in children compared to in adults [ 25 ].…”
Section: Therapeutic Considerations: Past and Futurementioning
confidence: 99%
“…However, a large meta-analysis of 10 trials including 1661 patients with pediatric AML showed a shorter OS for FLT3-ITD mutated AML [ 31 ]. AIEOP-BFM AML 2020 proposed risk stratification in three groups (standard, intermediate, and high-risk AML); AML is high risk when minimal residual disease (MRD) is ≥1% after induction course 1 or ≥0.1% at induction 2 or blast count is ≥5% at induction 1 (only if flow results are not informative) with one of genetic/molecular aberration at diagnosis, as described in Table 1 [ 24 ].…”
Section: Therapeutic Considerations: Past and Futurementioning
confidence: 99%
“…Although the current, highly intensive, chemotherapeutic regimens used in pediatric acute myeloid leukemia (AML) have contributed to immense improvement in overall survival rates [1][2][3], the associated serious treatment-related toxicities remain an important concern [4,5]. In particular, the chemotherapy-induced severe and prolonged neutropenia predisposes patients to bacterial and fungal infections, which may cause life-threatening complications throughout treatment and significant treatment delay [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%